2018
DOI: 10.1093/cid/ciy169
|View full text |Cite
|
Sign up to set email alerts
|

Significant Patient Impact Observed Upon Implementation of Point-of-Care Early Infant Diagnosis Technologies in an Observational Study in Malawi

Abstract: We conducted an observational study in Malawi to understand the patient impact of implementing point-of-care early infant diagnosis (POC EID). Antiretroviral treatment initiation rates were significantly improved with the implementation of same-day POC EID testing compared with referred, longer-turnaround laboratory-based testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
49
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 14 publications
8
49
1
Order By: Relevance
“…HIV‐positive infants were nearly twice as old as the HIV‐negative infants (64.5 vs. 33 days) at the time of sample collection. Similar data were observed previously . No test requisition forms indicated that the specimen was a later testing timepoint in the early infant diagnosis algorithm.…”
Section: Discussionsupporting
confidence: 85%
“…HIV‐positive infants were nearly twice as old as the HIV‐negative infants (64.5 vs. 33 days) at the time of sample collection. Similar data were observed previously . No test requisition forms indicated that the specimen was a later testing timepoint in the early infant diagnosis algorithm.…”
Section: Discussionsupporting
confidence: 85%
“…Testing infants earlier (at birth) and with a more efficient point of care (POC) HIV diagnostic technology is emerging as a strategy to streamline EID, minimize challenges with traditional central laboratory-based PCR testing, and bridge the gap between EID demand and laboratory capacity. POC diagnostic technologies such as GeneXpert HIV-1 Qual [15] and Alere m-PIMA [16] are cartridge-based tests that can be processed at the hospital by trained clinical or laboratory staff and can result in more rapid turnaround times of results, more infants being identified as HIV-positive and more infants initiated on ART at younger ages than traditional testing strategies [17][18][19][20][21][22]. Studies have shown high sensitivity and specificity of POC testing and found that POC implementation is feasible in hospital-based settings in Kenya [23,24], South Africa [18,[25][26][27], Mozambique [28], and Tanzania [29]; is acceptable to providers [26] and patients [30]; and may be a cost-effective option for EID [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…POC VL testing improves turn‐around time (TATs) and retention in care among adults on ART [8], while POC EID testing reduces TATs and time to ART initiation in infants [9‐14]. Both have potential to reduce morbidity and mortality among pregnant WLHIV and their infants.…”
Section: Introductionmentioning
confidence: 99%